Factors that influence clinical trial participation by patients with cancer in Australia: a scoping review protocol. Issue 4 (6th April 2022) - You, Kyung Ha; Lwin, Zarnie; Ahern, Elizabeth; Wyld, David; Roberts, Natasha
Abstract : Introduction: Clinical trials are the backbone of research. It is well recognised that patient participation in clinical trials can be influenced by a myriad of factors such as access to a clinical trial, restrictive trial eligibility criteria and perceptions held by patients or physicians about clinical trials. Australia is a key stakeholder in the global clinical trials sphere. This scoping review protocol aims to identify and map the current literature describing factors that influence clinical trial participation of patients with cancer, in Australia. Methods and analyses: The Joanna Briggs Institute (JBI) methodology for scoping reviews will be used to conduct this review. Four electronic databases will be systematically searched for relevant published literature on this topic, as a collaborative process involving the lead investigator and a health science librarian. We will hand search of citations and reference lists of the included papers, and a grey literature search through Google scholar, Grey Literature Report, Web of Science Conference Proceedings. All published papers pertaining to patients diagnosed with solid organ or haematological malignancies will be included. Studies which did not involve patients from Australia will also be excluded. A customised data extraction tool will be pilot tested and refined, and subsequently two independent reviewers will perform data screening and extraction. Results will be collated and reported following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) extension for scoping reviews: PRISMA-Scoping Reviews. Quantitative data will be presented using descriptive statistics. Qualitative data will be synthesised using thematic analyses. This scoping review does not require ethical approval as the methodology focuses on analysing information from available published data. Ethics and dissemination: Results will be disseminated to relevant stakeholders including consumers, clinicians, professional organisations and policy-makers through peer-reviewed publications and national and international conferences.